Advances and Challenges in Intranasal Delivery of Antipsychotic Agents Targeting the Central Nervous System - Pandey, Manisha; Jain, Neha; Kanoujia, Jovita; Hussain, Zahid; Gorain, Bapi (Frontiers in Pharmacology, 2022)
Treatment of central nervous system disorders is challenging using conventional therapies because of the presence of the blood-brain barrier (BBB). This BBB restricts the permeation of most of the therapeutics targeting the brain because of its impervious characteristics. Advancement of drug delivery tools and delivering these tools using the intranasal route of drug administration have shown the potential of circumventing BBB, thereby delivering the therapeutics to the brain at a significant concentration with minimal exposure to the systemic circulation. This phenomenon of novel strategies could lead to improved efficacy of antipsychotic agents using several advanced drug delivery tools while delivered via intranasal route. An overview of this intranasal route in overcoming the biological barrier of BBB has been focused on in this review. Preclinical and clinical advancements on the delivery of antipsychotics using this intranasal route have also been emphasized.